Implementation of Pharmacogenomic Information on Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis - Tsukagoshi, Eri; Tanaka, Yoichi; Saito, Yoshiro (Frontiers in Medicine, 2021)
Drug-related Stevens-Johnson syndrome and toxic epidermal necrolysis (SJS/TEN) are rare but severe adverse drug reactions, termed as idiosyncratic reactions; however, predicting their onset remains challenging. Pharmacogenomic information associated with SJS/TEN has accumulated on several drugs in the last 15 years, with clinically useful information now included on drug labels in several countries/regions or guidelines of the Clinical Pharmacogenetics Implementation Consortium (CPIC) for implementation. However, label information may differ among countries. This mini-review summarizes pharmacogenomic information on drug labels of 5 drugs in six countries and compared descriptions of drug labels and CPIC guidelines. Finally, we discuss future perspectives of this issue. Pharmacogenomic information on drug labels is not well harmonized across countries/regions, but CPIC guidelines are a scientifically sound goal for future pharmacogenomic implementation.